Biomechanical comparison of titanium miniplates versus a variety of CAD/CAM plates in mandibular reconstruction. (November 2020) - Steffen, Claudius; Sellenschloh, Kay; Vollmer, Matthias; Morlock, Michael M.; Heiland, Max; Huber, Gerd; Rendenbach, Carsten
Abstract : Background: Titanium plate fixation of free flaps in mandibular reconstruction involves complications such as osseous non-union or imaging artefacts. Interosteotomy movement (IOM) is known to affect bone healing. This study aimed to compare IOM and mechanical integrity of four different fixation systems in a mandible reconstruction model. Methods: Two polyurethane (PU) fibula segments were fixed in right-sided defects of PU mandibles. Laser-melted patient-specific titanium plates were fixed with non-locking-screws (Ti-NL) or locking-screws (Ti-L). The third group consisted of locking-screws for patient-specific polyetheretherketone (PEEK-L) plates. The last group used titanium miniplates and monocortical screw fixation (Ti-MP). All models were loaded unilaterally via cyclic dynamic loading with increasing loads to simulate mastication. IOM was registered using a 3D optical tracking system. Findings: PEEK-L showed highest vertical displacement (p = 0.010), lowest stiffness (p = 0.004) and highest IOM (p = 0.001). All specimen in PEEK-L demonstrated abnormal bending (n = 5) or plate fracture (n = 1). Vertical displacement or stiffness did not differ between any of Ti-MP, Ti-L and Ti-NL. IOM in Ti-MP was higher than in Ti-L and Ti-NL (p = 0.001). Interpretation: Mechanical integrity of all titanium plates complies with established standards. In this model, the screw system did not influence IOM. In the tested composition and shape, PEEK plates do not seem to guarantee sufficient mechanical integrity for a use in mandibular reconstruction. Thus modifications are needed. Future clinical studies are needed to clarify optimal IOM after mandible reconstruction. Graphical abstract: Image 1